THE IMPLEMENTATION OF DEEP DIALOGUE LEARNING MODEL BASED ON THE STRUGGLE OF ANAK AGUNG GDE ANOM MUDITA TO INCREASE CRITICAL THINKING AND HISTORY LEARNING OUTCOME - A. A Gek Indah Ani; Ruli Anto; Ida Bagus Brata; Lianda Dewi Sartika (Unmas Press, 2022)
The aims of this study are to 1) find out the benefits of the deep dialogue learning model in improving students' critical thinking skills 2) find out the benefits of the deep dialogue learning model in improving student learning outcomes 3) find out the benefits of the deep dialogue learning model based on local historical actor Anak Agung Gde Anom Mudita in improving critical thinking ability and the learning outcomes. The research subjects were students of class X IPS 1 SMA Negeri 6 Denpasar totaling 36 students. The object of this research is the students' historical learning outcomes and critical thinking skills. Data collection techniques are conducted by tests and non-tests. The research instrument used in this research is a questionnaire, observation, interviews and test questions. The results showed: that the first cycle of learning outcomes was 61.7 and the second cycle increased to 75.55. The achievement of KKM has increased from the initial condition of 58.33% to 80.55%. The improvement of critical thinking ability resulted from the questionnaire score increased from the initial condition of 1714 to 2830 in the final condition. The conclusion of this study is that the deep dialogue learning model based on local historical actor Anak Agung Gde Anom Mudita can improve learning outcomes and critical thinking abilities of students in class X IPS 1 SMA Negeri 6 Denpasar.